Bridged triarylboranes, -silanes, -amines, and -phosphines as minimalistic heteroatom-containing polycyclic aromatic hydrocarbons: Progress and challenges - Schaub, Tobias A.; Padberg, Kevin; Kivala, Milan (Journal of physical organic chemistry, 2020)
Minimalistic heteroaromatic scaffolds result from the introduction of various ortho-bridging moieties into triarylboranes, -silanes, -amines, and -phosphines. This molecular design opens an avenue to a class of structures fascinating not only from a fundamental standpoint, but also because of their aptitude to serve as active materials in organic electronics. In this Review, the history of these conceptually simple heteroatom-containing π-systems is briefly summarized, and the current state-of-the-art in this vividly expanding field of research is discussed. The synthetic strategies towards these scaffolds are covered together with their structural and electronic traits. Special focus is dedicated to the recent progress and challenges in the molecular design of functional materials made thereof.
First published: 22 November 2019
Gesehen am 18.01.2021